Genotype x hypoxia interaction in endurance performance - Masschelein, E.; Ramaekers, M.; Van Thiennen, R.; Hespel, P.; Thomis, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Physiological adaptations to hypoxia have been extensively studied. However, these adaptations are marked by strong variation (Martin et al., 2010). Factors that contribute to this variation are poorly understood. We examined the importance of genetic factors in inter-individual variability in responses to hypoxia using a monozygotic (MZ) genotype x hypoxia (G x H) interaction twin design. Methods: Twenty-seven healthy male subjects (age: 24.9 ± 4.4 years) of which 12 MZ twins pairs and one MZ triplet participated in an experimental session in normoxia (20.93% O2) and severe hypoxia (11% O2, ~5000m altitude) in a normobaric hypoxic facility. During the first 5-h rest period, oxygen content was held constant at 20.93% in normoxia while in hypoxia oxygen content was progressively decreased from 20.93% to 11%. Following a 5-h rest period, a 3-h experimental protocol started consisting of a 1-h rest period, a 30-min reaction time test, a 20-min submaximal cycling exercise (SUB, 1.2 W/kg body weight) and a maximal incremental exercise (MAX, 50W + 20W/min). Acute mountain sickness (AMS) symptoms were assessed using the Lake Louise Scoring System at the end of the protocol. G x H was tested by a two-way analysis of variance for repeated measures (twins x hyp/normoxic condition) and refers to a phenotype for which the response to hypoxia is significantly influenced by genetic variation. Results: At rest and SUB, hypoxia per se increased heart rate (HR), minute ventilation (VE), carbon dioxide output (VCO2), respiratory exchange ratio (RER) and blood lactate (La) (P<0.01) and decreased oxygen saturation (SpO2) (P<0.001). At MAX, hypoxia decreased peak HR, SpO2, VE, VO2, VCO2, La and time to exhaustion (P<0.001) and increased RER (P<0.05). In hypoxia, the severity of AMS increased (P<0.001) and the incidence of AMS was 26%. In response to hypoxia, there were considerable differences between subjects. However, this was not randomly distributed among subjects. Significant G x H was found at rest for HR, SpO2 and RER (ICC = 0.79 - 0.85, F-ratio = 3.8 - 5.6, P<0.05), at SUB for HR, SpO2 and La (ICC = 0.75 - 0.89, F-ratio = 2.9 - 8.0, P<0.05) and at MAX for HR, SpO2, La, VO2, VCO2, RER (ICC = 0.74 - 0.91, F-ratio = 2.9 - 10.4, P<0.05). Significant G x H was found for change in time to exhaustion (ICC = 0.74, F-ratio = 2.84, P<0.05). Furthermore, significant G x H was found for the severity of AMS (ICC = 0.74, F-ratio = 2.84, P<0.05). Conclusion: These results strongly suggest that a genetic component is involved in the response to hypoxia.